Strategic and operational factors influence on building maintenance management operation process in office high rise buildings - Yahya, Mohamad Ridzuan; Ibrahim, Md. Najib (2010)
The main objective of this paper is to examine strategic and operational factors influencing building maintenance management operation processes in office high rise buildings. Four factors are identified in building maintenance management: building maintenance policy, strategic management, facility management and performance management. The building maintenance management operation processes is the key for providing better built environment to building owner, tenants, occupants and maintenance professionals. It is particularly important in managing hospitality facilities in office high rise buildings. However, planned maintenance and unplanned maintenance are not in a high priority list in most of the organizations. This barrier contributes to the gaps between top management at the strategic level and maintenance personnel at the operational level. Building maintenance is changing pace with the development of facility management, which has impacts on the planning to implementation of maintenance operation processes and building performance. The information related to the strategic and operational factors is essential before an in-depth study is undertaken about the improvement of the gaps between top management at the strategic level and maintenance personnel at the operational level for building operation efficiency.